HUKUM MENCERAIKAN WANITA DALAM KONDISI HAMIL: KERANGKA KONSEPTUAL DAN PENERAPANNYA - Zuhri Zuhri (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
In divorce from a pregnant woman, there are many reasons for the husband to leave his wife pregnant, one of which is related to there are many rifts and disharmony in the household when the wife is pregnant. This article focuses on the discussion of the law of divorcing women in pregnant conditions. The first part is to explore the understanding of the concept of divorcing pregnant women through the perspective of Islamic law and religious courts regarding the case and the factors that influence it. Research in this study is qualitative. This research method is descriptive-analytical, which describes and explains the problem of divorce of pregnant women accordance with the views of Islamic law and the views of religious courts. The result of this study is that the law of talak women is pregnant according to Islamic law, and there is disagreement about punishing tarak problems in the pregnant state. With different arguments, some argue that talak in this state of pregnancy is not allowed, while others argue that this is permissible. In the case of divorce of religiously pregnant women there are those who say it is permissible and some say it is forbidden, and want to divorce in a holy state and do not bear the burden. Meanwhile, according to the law, religious courts are allowed under certain legally applicable conditions. But what the husband needs to know is that dropping the talak to his wife must choose a good time.